GAGASAN DEKRIMINALISASI TERHADAP PASAL 505 KITAB UNDANG-UNDANG HUKUM PIDANA TENTANG TINDAK PIDANA GELANDANGAN - Bagus, M. Rizky; Erdianto, Erdianto; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Article 505 of the Criminal Code states that "Any person who is stranded without seeking, shall be punished for committing homelessness with a maximum imprisonment of three months". From this article it means that homelessness is a criminal act that is punishable by crime. On the other hand, Article 34 of the 1945 Constitution confirms that the poor and neglected children are cared for by the state, it can be seen from the two articles that there is a conflict between the articles of the 1945 Constitution and the Criminal Code. In addition, in criminal law, there is a principle of geen straf zonder schuld, this principle requires the existence of an element of mens rea in the perpetrator, that mistakes are the main element of a person can be convicted, from this principle it proves that there is no clear correlation between vagrant behavior and the elements mens rea in homeless people. The purpose of this study is to determine the need for decriminalization of article 505 of the Criminal Code.This research is a normative study with an approach to the legal principle, namely the principle of geen straf zonder schuld. Using secondary data with data collection from library research (library research), in qualitative juridical analysis and concluded using a descriptive analysis method.From the research results it can be seen that criminalization in Indonesia is still confusing, the laws in Indonesia still do not pay attention to important aspects of the criteria for criminalization and decriminalization. As well as the application of the geen straf zonder schuld principle to Article 505 of the Criminal Code is not applied so that non-criminal homelessness is said to be a crime by law. So the conclusion of the problem is an idea that requires the actions of the homeless to be decriminalized. The process of decriminalizing homeless people has an important meaning, namely improving the conditions of the Criminal Code which are considered outdated and will return the criminal law to its original position, namely as ultimum remedium.Keywords: Homeless-Crime-Criminalization-Decriminalization-Geen Straf Zonder Schuld